Rolling horizon optimization for real-time operation of prosumers with Peer-to-Peer energy trading. (March 2023) - Wang, Xiaoyu; Wang, Zibo; Mu, Yunfei; Deng, Youjun; Jia, Hongjie
Abstract: Peer-to-Peer energy trading is recognized as a promising approach for prosumers to improve the operational economics. However, the uncertainty of renewable energy poses challenges to the reliable and economical operations of prosumers. This paper focuses on the real-time operation of prosumers. An efficient rolling horizon optimization-based real-time operation strategy for prosumers is proposed to minimize the total operational cost in one-day, in which the thermal comfort demand of the prosumers is also considered. The case study is finally conducted for 94 prosumers located at an urban community microgrid in a typical summer day scenario. Simulation results show that the proposed rolling horizon operation strategy can make full use of the flexible energy resources of prosumers, realizing the local energy supply–demand balance while improving prosumers' operational economics. Moreover, the negative impact of day-ahead forecasting errors on the intra-day operation can be reduced significantly.